Fuzzy pairs in fuzzy α-lattices - Payal A. Khubchandani; Meenakshi P. Wasadikar (Journal of Hyperstructures)
In this paper, we introduce the notion of a fuzzy αmodular pair in a fuzzy α-lattice and obtain some results.